BRAVERY, PERSISTENCE, INTEGRITY, AND VITALITY ON ADVERSITY QUOTIENT: STUDY ON HIGH SCHOOL STUDENTS - Utami, Sri; Wangid, Muhammad Nur (JURNAL EDUSCIENCE, 2025)
Purpose – This study aims to describe and investigate the influence of bravery, persistence, integrity, vitality, and adversity quotient in adolescent high school students in Tarakan City.Methodology–This study employs a correlational design with a quantitative approach. A total of 370 students were selected as the sample. The sampling method applied was proportionate stratified random sampling. Data were collected using a scale-based instrument. Reliability testing was conducted using Cronbach's alpha method for the Adversity Quotient, Bravery, Persistence, Integrity, and Vitality. Data analysis involved the use of descriptive statistics and multiple regression analysis, performed using SPSS version 26 for Windows.Findings – The findings indicate a statistically significant correlation between the variables of Bravery, Persistence, Integrity, and Vitality with the Adversity Quotient (AQ) at a 5% level of significance. (1). bravery has a positive relationship with AQ. (2) Persistence has a significant effect on AQ. (3) Integrity also has a significant effect. (4) Vitality has a significant effect on AQ. When examined collectively, these four variables significantly contribute to the prediction of AQ, as indicated by an F-value of 206.475, which exceeds the F-table value of 2.396, with an R-squared value of 0.694. The model accounts for 69.4% of the variance in Adversity Quotient, while other unexamined factors may explain the remaining 30.6%. When examined collectively, these four variables significantly contribute to the prediction of AQ.Significance – This research is expected to enrich scientific insight in the field of guidance and counseling, particularly regarding its influence on high school students in Tarakan City, as well as the description of adversity quotient, bravery, persistence, integrity, and vitality.